2016
DOI: 10.1038/ncomms11765
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Deep Water Production during the Last Glacial Maximum

Abstract: Changes in deep ocean ventilation are commonly invoked as the primary cause of lower glacial atmospheric CO2. The water mass structure of the glacial deep Atlantic Ocean and the mechanism by which it may have sequestered carbon remain elusive. Here we present neodymium isotope measurements from cores throughout the Atlantic that reveal glacial–interglacial changes in water mass distributions. These results demonstrate the sustained production of North Atlantic Deep Water under glacial conditions, indicating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
147
1
10

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(181 citation statements)
references
References 60 publications
18
147
1
10
Order By: Relevance
“…This remains true in the glacial state for the Nordic and Labrador seas, but further south the contribution of NADW dwindles rapidly below 2 km depth. This simulated contraction of NADW co-occurs with the volumetric expansion of underlying Antarctic waters, and is consistent with the many paleoceanographic observations for shoaled NADW in the glacial North Atlantic (Curry and Oppo 2005;Adkins 2013;Lippold et al 2016), although it does not preclude the possibility that part of the apparent shoaling reflects a change in the remineralized carbon content of AABW (Gebbie 2014;Howe et al 2016). We also note the interesting possibility that, under glacial conditions, the Labrador Sea produced dense bottom waters that trickled downslope analogous to the modern Antarctic (Keigwin and Swift 2017), and which the model is incapable of simulating.…”
Section: Glacial Water Mass Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…This remains true in the glacial state for the Nordic and Labrador seas, but further south the contribution of NADW dwindles rapidly below 2 km depth. This simulated contraction of NADW co-occurs with the volumetric expansion of underlying Antarctic waters, and is consistent with the many paleoceanographic observations for shoaled NADW in the glacial North Atlantic (Curry and Oppo 2005;Adkins 2013;Lippold et al 2016), although it does not preclude the possibility that part of the apparent shoaling reflects a change in the remineralized carbon content of AABW (Gebbie 2014;Howe et al 2016). We also note the interesting possibility that, under glacial conditions, the Labrador Sea produced dense bottom waters that trickled downslope analogous to the modern Antarctic (Keigwin and Swift 2017), and which the model is incapable of simulating.…”
Section: Glacial Water Mass Characteristicssupporting
confidence: 86%
“…An Antarctic origin of these salty bottom waters would be consistent with reconstructions of the chemical composition of deep waters, primarily reflected by isotopic ratios in the shells of fossil benthic foraminifera. Both the stable carbon isotope ratio, δ 13 C (Boyle and Keigwin 1982;Duplessy et al 1984;Sarnthein et al 1994;Curry and Oppo 2005) and neodymium isotope ratio, εNd (Piotrowski et al 2005;Howe et al 2016) indicate that dramatic changes occurred in the Atlantic basin, with a volumetric expansion of the Antarctic chemical fingerprint under glacial conditions. Although the δ 13 C evidence is not unambiguous (Gebbie 2014), when viewed together with the spatial distribution of εNd changes, there is strong indication that the penetration depth of North Atlantic Deep Water (NADW) was reduced during the LGM (Lippold et al 2016).…”
mentioning
confidence: 99%
“…The new C isotope results support the same conclusion based on Nd isotopes (20). If this new source of bottom water resulted from brine rejection and not heat loss to the atmosphere, there may not have been the same climate impact as modern NADW production.…”
supporting
confidence: 76%
“…For example, Pa/Th results (2) and Nd results (17) from BR consistently show that the glacial mixture of bottom water must have contained a northern component. This finding is at variance with the prevailing view that there was little or no northern deep water present in the glacial North Atlantic (18,19), but a recent synthesis of Nd isotopes in the western Atlantic has also been interpreted as evidence for a glacial source of NADW (20). Furthermore, Böhm et al (21) found that some interstadials and the last interglacial on BR had lower eNd than in the modern ocean.…”
mentioning
confidence: 77%
“…Variations in the isotopic signature of Neodynium, for instance, indicate that AABW was more dominant in the deep ocean during the LGM and that its mixing with a glacial form of North Atlantic Deep Water (NADW) was more intense (Howe et al, 2016). These and other authors (Burckel et al, 2016) find further support for the presence of a shallower AMOC above 2500 m. Moreover, simulated distributions of carbon isotopes across a range of idealised circulations have shown that a shallower AMOC is necessary to optimise model-proxy agreement at the LGM (Menviel et al, 2016).…”
Section: Meridional Overturning Circulationmentioning
confidence: 99%